Breeding Progress for Vitamin A, Iron and Zinc Biofortification, Drought Tolerance, and Sweetpotato Virus Disease Resistance in Sweetpotato - Mwanga, Robert O.M.; Swanckaert, J.; Silva Pereira, G. da; Andrade, M.I.; Makunde, G.S.; Grüneberg, W.J.; Kreuze, Jan F.; David, M.; Boeck, B. de; Carey, E.E.; Ssali, R.T.; Utoblo, Obaiya; et al. (Frontiers Media, 2021)
Sweetpotato is a resilient food crop with great potential to contribute to reduced hunger in the world. Sweetpotato shows significant potential to contribute to reducing the Global Hunger Index, which reflects deficiencies in calories and micronutrients based on the components of hunger, undernourishment, under-five mortality rate, stunting and wasting. Its genetic diversity has been harnessed through breeding to increase vitamin A, iron, and zinc content, virus resistance and climate resilience for the world's food needs. Africa and India are the most food-insecure regions. The main objectives of this research were to: provide information and a knowledge base on sweetpotato breeding in Africa for biofortification of vitamin A, iron, and zinc, drought tolerance and virus resistance; recommend procedures for generating new breeding populations and varieties; and develop new tools, technologies and methods for sweetpotato improvement. The research was implemented between 2009 and 2020 in 14 collaborating African countries using introduced and local genotypes. The redesigned accelerated breeding scheme resulted in increased genetic gains for vitamin A, iron, zinc contents and virus resistance, and the release by sub-Saharan African countries of 158 varieties; 98 of them orange-fleshed; 55 varieties bred by an accelerated breeding scheme; 27 drought-tolerant and two with enhanced iron and zinc content. Our experience has demonstrated that through the use of more optimized, standardized and collaborative breeding procedures by breeding programs across Africa, it is possible to speed official sweetpotato variety release and contribute to reducing the severe micronutrient deficiencies on the continent.